Sources of support for women experiencing obstetric fistula in northern Ghana: A focused ethnography. (September 2016) - Sullivan, Ginger; O'Brien, Beverley; Mwini-Nyaledzigbor, Prudence
Abstract: Objective: we explored how women in northern Ghana who have or have had obstetric fistula and those close to them perceive support. Design: focused ethnography, that includes in-depth interviews, participant observation, and scrutiny of relevant records. Setting: a fistula treatment centre in a regional urban centre and three remote villages located in northern Ghana. Participants: the sources of data included in-depth interview ( n =14), non-participant observation and interaction, as well as scrutiny of relevant health records and documents. Participants for in-depth interviews and observation included women affected by obstetric fistula, their partners, parents, relatives, nurses and doctors. Findings: presentation of obstetric fistula information, particularly by Non-Governmental Organisations was not in a format that was readily understandable for many women and their families. Food and other basic requirements for daily living were not necessarily available in the fistula treatment centre. Travelling for care was costly and frequently not easily accessed from their communities. Fistula repair surgery was available at unpredictable times and only for a few days every one to two months. Conclusions: women perceived support from spouses/partner, family members, and other relatives but much of this is limited to tangible support. Perceptions of support were particularly focused on access to information and finances. Implications for practice: the implementation of strategies to increase support for women living with obstetric fistula include improving access to fistula repair treatment, directing resources to create a dedicated specialist fistula centre located where most cases of OF occur and providing education to front-line workers. Strategies to prevent fistula as well as identify and support safe motherhood practices are needed for women affected by obstetric fistula.